Effect of loading strain rate on creep and stress-relaxation characteristics of sandy silt - Amin Chegenizadeh (Results in Engineering, 2020)
Silty soil is abundant in alluvium deposits within urban areas, and determination of its long-term settlement characteristics is a crucial issue. This study aims to investigate the effect of four different strain rates (i.e., 1, 0.1, 0.01, 0.001 ​mm/min) on the creep and stress-relaxation behaviour of a natural type of sandy silt by performing a series of triaxial compression tests. In monotonic (reference) tests, the peak deviatoric stress increased and the volumetric strain decreased by increasing the shearing rate. The results in greater shearing rates showed that the deviatoric stress curves have a greater quasi-elastic behaviour followed by a slight yield point. Also, an almost uniform behaviour was recorded in the deviatoric stress of the specimens tested at lower shearing rates. The creep testing showed that the specimens tested at greater initial shearing rates have a greater axial strain than those tested at lower shearing rates. Also, the stress-relaxation testing showed that the specimens tested at higher shearing rates have a greater relaxation than the specimens tested at lower initial shearing rates. A comparison between particle breakages that occurred in each testing condition showed that the particle breakage index (PBI) in a monotonic condition is 1.25 and 1.5 times (in average) greater than the creep and stress-relaxation tests respectively.